Ghana, Accra Urban Food and Nutrition Security, 1997 - International Food Policy Research Institute (International Food Policy Research Institute, 2000)
This dataset provides information on livelihoods and household food and nutrition security in an urban setting. The questionnaire was administered to 559 households in 16 enumeration areas in the Greater Accra Metropolitan Area from January through April, 1997. The sample is representative of households with children under 36 months. Topics in the household survey include complete household income, including information on credit and transfers; employment status; household food consumption (including detailed information on street food consumption); household food and non-food expenditures, assets; educational attainment for the head of the household and the mother of the index child, morbidity and health seeking behavior; anthropometry of all children in the household and the mother of the index child; care practices; food coping strategies; adaptive strategies; and hygiene spot check. Topics in the community survey include market prices, street foods, quality of services, and NGO activity.